O direito a saúde e a um meio ambiente favorável ao trabalho e aos trabalhadores - Maciel, Joelson de Campos (2012)
Environmental law of labor in Brazil is intended primarily to protect worker health, but such protection is limited positivity in practice, if only to prevent and combat disease, and its evident environmental risks. We understand that protecting the health of the worker will look beyond this series and aims a new constitutional order dedicated to the promotion of social rights as well as environmental, in order to compose the concept of human dignity in an ecologically balanced environment for a systemic view of the social right to health and environmental law corresponding to a healthy quality of life within their existential project, as provided, in particular, Article 225 of the Constitution of the Federative Republic of Brazil, as well as international treaties related to human rights protection of health in which Brazil is a signatory and conventions and recommendations of the International Labour Organisation - ILO. Moreover, to understand the real meaning of working environment and their health category of the worker it is also necessary to carry out some studies of the philosophical, looking for the very meaning of human dignity today, its purposes, the collective action and obligations the state.